Incidence of and risk factors for liver damage in patients with HIV‐1 mono‐infection receiving antiretroviral therapy. (15th March 2022) - Huang, Huihuang; Song, Bing; Gao, Lin; Cheng, Juan; Mao, Yufeng; Zhao, Hua; Tu, Bo; Huang, Shun; Zhang, Jieli; Chen, Dianjie; Zhao, Peng; Jiao, Yan‐Mei; et al.
Abstract: Objectives: The study aimed to investigate the incidence of and risk factors for liver damage in patients with human immunodeficiency virus type‐1 (HIV‐1) mono‐infection receiving antiretroviral therapy (ART). Methods: We retrospectively analyzed the clinical data of patients who were diagnosed with HIV‐1 infection and initiated ART from January to December 2017. Among them, 382 patients with HIV‐1 mono‐infection and normal baseline liver function were included in the analysis. The incidence of liver damage at each follow‐up point, and possible risk factors for liver damage were evaluated via COX regression survival analyses. Results: The overall incidence of liver damage (grade I–IV) was 27.23% (interquartile range [IQR]: 26.38%–28.72%). Grade I liver damage was most common and accounted for 22.13% of cases (IQR: 21.06%–24.04%), while grade II liver damage accounted for 3.40% of cases (IQR: 3.19%–4.26%). COX regression and survival analyses revealed that baseline body mass index (BMI), alanine aminotransferase (ALT) level, CD4 + T cell count, HIV‐1 viral load, and the antiretroviral regimen were significantly correlated with the occurrence of liver damage. Moreover, baseline ALT levels and HIV‐1 viral load were identified as independent risk factors for liver damage in patients with HIV‐1 mono‐infection. Conclusion: Liver damage is common in patients with HIV‐1 mono‐infection undergoing ART. Patients with risk factors for liver damage should be well‐informed before the initiation of ART, and liver function should be closely monitored during ART even in patients with normal liver function before ART.